Orddannelsesstrukturen af danske kentaurnominaler - Rajnik, Eugeniusz (Folia Scandinavica Posnaniensia, 2009)
The present paper reviews different approaches to a type of morphological constructions called kentaurer in Danish. These morphological formations, also referred to as kentaurnominaler or gerundiumformer are productive in the language. The paper offers a morphological classification of these constructions.